2023
DOI: 10.1021/acsanm.3c03852
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–SiO2 Hybrid Nanoparticles with Enhanced Radical Stabilization and Biocide Activity

Fotini Fragou,
Areti Zindrou,
Yiannis Deligiannakis
et al.

Abstract: Nanocarbon and nanosilica are widely-used nanomaterials of significant industrial interest. Herein, a library of {carbon–SiO2} hybrid nanoparticles, with controlled nanocarbon content and sp3/sp2 profile, was engineered by a flame spray pyrolysis (FSP) process in one step. Their structure–function relationship was evaluated by studying their radical-generation and radical-stabilization activities, using electron paramagnetic resonance spectroscopy in tandem with their biocide activity toward marine bacteria Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…More specifically, the G band at ∼1580 cm –1 is attributed to stretching of the sp 2 -bonded carbon atoms in graphitic-type structures, while the D band is correlated to sp 3 carbon atoms due to defects or disorder, presented in graphitic structures . The intensity ratio I D / I G can serve as a metric of the graphitization degree of the nanocarbon layers . The I D / I G ratios listed in Table show a nonmonotonous trend.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, the G band at ∼1580 cm –1 is attributed to stretching of the sp 2 -bonded carbon atoms in graphitic-type structures, while the D band is correlated to sp 3 carbon atoms due to defects or disorder, presented in graphitic structures . The intensity ratio I D / I G can serve as a metric of the graphitization degree of the nanocarbon layers . The I D / I G ratios listed in Table show a nonmonotonous trend.…”
Section: Resultsmentioning
confidence: 99%
“…A library of four SrTiO 3-x (for convenience, these are codenamed STO) perovskites was prepared in an enclosed single-nozzle FSP reactor using two different Anoxic-FSP configurations (see Figure 1 A,B). The A-FSP reactor set-up uses CH 4 to control the anoxic-combustion environments, as exemplified in our recent works [ 16 , 26 , 27 ]. This CH 4 is additional to the classically used CH 4 in the pilot-flame of FSP [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The two A-FSP configurations in Figure 1 A,B are codenamed Radial- and Axial-A-FSP; these define the way in which CH 4 is introduced, respectively. In all cases, the FSP-nozzle was enclosed by a cylindrical metal chamber consisting of two concentric tubes, a sinter metal tube (outer tube) and a perforated metal tube (inner tube) to isolate the flame from the surrounding atmosphere, as has been described in detail in previous works [ 16 , 26 , 27 , 29 ]. The so-produced materials (listed in Table 1 ) are codenamed STO-R and STO-A for Radial- and Axial-A-FSP, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent work, we proposed the A-FSP technology to engineer carbon-SiO 2 nanocomposites. As shown, control of the type and amount of carbon by A-FSP allowed tuning of the properties of the SiO 2 matrix. Our detailed study revealed structure–function relationships with a focus on the biocidal activity of the C-SiO 2 composites.…”
Section: Introductionmentioning
confidence: 99%